2016
DOI: 10.1161/circimaging.116.004815
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling in Patients With Primary and Secondary Aldosteronism

Abstract: P rimary aldosteronism (PA) is a common curable cause of high blood pressure (BP) characterized by undetectable renin and angiotensin II, and an excess rate of metabolic syndrome, 1 cardiovascular damage, 2,3 and events. 4,5 Secondary aldosteronism (SA) is a common feature of conditions characterized by effective circulating volume, causing cardiovascular underfilling as heart failure, nephrotic syndrome, and liver cirrhosis. 6 The latter also features low systemic vascular resistance owing to splanchnic vasod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…Furthermore, it is also in accordance with the report of a relationship of excess PAC with LV hypertrophy, regardless of the elevation of blood pressure. [14] …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also in accordance with the report of a relationship of excess PAC with LV hypertrophy, regardless of the elevation of blood pressure. [14] …”
Section: Discussionmentioning
confidence: 99%
“…64 The PA patients had increased LV mass, high prevalence of LVH, inappropriate LV mass, subclinical LV systolic and diastolic dysfunction. The patients with secondary hyperaldosteronism (due to liver cirrhosis) also show increased LV mass, high prevalence of LVH and diastolic dysfunction, but not subclinical systolic dysfunction.…”
Section: The ‘Upstream’ Therapy Of Af and The Randomized Clinical Trimentioning
confidence: 94%
“…The work overload caused by a hyper-dynamic circulatory state and the high renin with ensuing hyperaldosteronism could be driving these changes in patients with liver cirrhosis. 64 Thus, in both PA and secondary hyperaldosteronism, aldosterone contributes to LVH and also cardiac fibrosis, causing LV diastolic dysfunction, increased atrial afterload, with ensuing atrial stretching, and wall stress, favoring AF onset. 64,65 …”
Section: The ‘Upstream’ Therapy Of Af and The Randomized Clinical Trimentioning
confidence: 99%
“…8,9 Animal models of PA and SA have demonstrated that myocardial fibrosis occurs in both forms of hyperaldosteronism, whether or not hypertension is present. 10 With this background, we will examine the interesting article by Cesari et al 11 in this issue of Circulation: Cardiovascular Imaging. Their purpose was to investigate whether PA and SA, which both feature high aldosterone levels, but different hemodynamic loads and plasma renin levels, are associated with different echocardiographic phenotypes.…”
Section: See Article By Cesari Et Almentioning
confidence: 99%
“…A plot of midwall shortening (FSmw, %) on the y axis vs end-systolic circumferential stress, an index of afterload, on the y axis, using methodology described in the study by Narayanan et al 19 The values for FSmw and circumferential stress were computed based on mean values for cardiac dimensions and blood pressure supplied by the authors 11 (NB: our methodology computes FSmw as values that are systematically higher than the authors' results for FSmw, but should be directionally similar. ); 95% confidence limits were derived from normal controls in our laboratory.…”
Section: Figurementioning
confidence: 99%